STUDY MODE DIFFERENCES IN STUDENT’S PERCEPTION OF EDUCATION SERVICE QUALITY IN SELECTED POLYTECHNICS IN NORTHERN NIGERIA - Abdullahi Sabo Muhammad; Maryam Ibrahim Abubakar (International Journal of Educational Excellence and Innovation, 2024)
This investigation was designed to determine student perception of Polytechnic education service quality dimensions in relation to their mode of study in Northern Nigeria. Six null hypotheses were constructed to guide the study. The quantitative research adopted the descriptive survey design method. The target population are all Polytechnic students studying different programs in Northern Nigeria. A sample size of 441 respondents were determined based Krejice and Morgan Table, and sampled using stratified random sampling technique. A structured questionnaire (SERVPERF) was adopted consisting of 27 items used in similar studies (Brochado, 2009; Cronin & Taylor, 1994, etc.) as tool for data collection. The tool was structured on five point Likert ratting pattern ranging from strongly disagree (1) to strongly agree (5). The composite reliability of the tool was .980 coefficient determined using Cronbach alpha method. Copies of the instrument were personally administered during classes and data were analyzed using both descriptive and inferential; statistics with the help of SPSS. The findings reveal that the level of students’ satisfaction was negative and insignificant, while the perceived level of loyalty was significant. There was significant relationship between each of the service quality dimension and student’s satisfaction, student satisfaction and loyalty. Students in evening/weekend and distance learning mode of study are more satisfied compared to their counterparts on full-time basis. Equally, older students who are more matured and experienced complain less than the younger ones. Based on all these, recommendations were made towards improving the service quality and customer satisfaction in Polytechnic education by the institution’s managers, administrators and policy makers and implementers.